Application of Artificial Neural Networks to Predict Monthly Targets for Receiving Section at PT. Indako Trading Coy Using the Backpropagation Method - farida Gultom (Marqcha Institute, 2023)
PT. Indako Trading Coy is a company engaged in the sale of motorcycles and spare parts with 1000 employees who are given work targets every month. Through the targets given, it can be predicted whether employees can be rewarded or not. Prediction is an important tool in determining everything to be effective and efficient. So far, a lot of forecasting is done intuitively using statistical methods. The choice of the method depends on various influencing aspects, namely aspects of time, data patterns, type of system model being observed, level of forecast accuracy or desired prediction and so on. The forecasting method used is using an artificial neural network (ANN) with the Backpropagation method.